Desarda repair versus Lichtenstein repair for treatment of inguinal hernia - Moghazy, Talal A.; Zayed, Yehia H.; Farid, Mona M. (International Surgery Journal, 2022)
Background: Inguinal hernias remain an important medical problem. The definitive treatment of all hernias is surgical repair. Desarda’s technique is a tension-free, mesh-free repair method that pays attention to the physiology of the inguinal region. Methods: This prospective comparative study was conducted in general surgery department at Al-Zahraa University Hospital and Damanhour Medical National Institute in the period between March 2019 and March 2021. It included 50 patients who were randomly divided into two equal groups: A (Desarda technique) and B (Lichtenstien technique). Results: The mean operative time in group A was 70.36 minutes and in group B was 64.88 minutes. Seroma formation occurred in 1 patient in group A (4%) while it occurred in 2 patients in group B (8%). The other postoperative complications were comparable in both groups during 1 year of follow-up, hernia recurrence occurred in 1 patient in group B (4%). Conclusions: Desarda repair of inguinal hernia is a good alternative to Lichtenstein repair.